THE IMPACT OF THE COVID 19 PANDEMIC ON COMPANY FINANCIAL PERFORMANCE (Case Study of a Food & Beverage Company listed on the IDX) - Mahrani, Wahdyan Sastria; Triyono, Triyono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aimed to compare the financial performance of companies before and during the COVID-19 pandemic in the food & beverage sector for the period 2019-2020. The population in this study consisted of 30 companies in the food & beverage sector. The sample included 19 companies obtained through purposive sampling that met the research criteria. The results of this study indicated a significant difference in the profitability ratio measured by Return on Assets before and during the pandemic. However, the liquidity ratio, solvency ratio, activity ratio, and market ratio did not show any significant differences during the COVID-19 pandemic. Keywords: Covid 19 Pandemic, Liquidity, Solvency, Profitability, Activity, Market Ratio